2022
DOI: 10.1177/07334648221099728
|View full text |Cite
|
Sign up to set email alerts
|

Using the Intersectionality-Based Policy Analysis Framework to Evaluate a Policy Supporting Sexual Health and Intimacy in Long-Term Care, Assisted Living, Group Homes & Supported Housing

Abstract: Sexuality is an integral part of being human throughout life. This does not change when moving into long-term care (LTC). However, the sexual health of persons living in LTC is often overlooked. This paper presents an analysis of the recently released health organizational policy: Supporting Sexual Health and Intimacy in Long-Term Care, Assisted Living, Group Homes & Supported Housing. The Intersectionality-Based Policy Analysis Framework is used to outline the policy problem, examine how this policy was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…( 16 ) We selected this framework to guide intervention adaptation and implementation planning based on the explicit emphasis on discussing values and creating a participatory and equity-based space for leading the project, as well as an emphasis on praxis – using an intersectional lens to change systems. ( 20 22 ) Recent studies have demonstrated the value of the IBPA framework,( 22 24 ) exemplified by its application to the U.S. COVID-19 policy response;( 20 ) which underscores the growing significance of considerations of intersectionality in public health and highlights the transformative shift from analysis to actionable strategies.…”
Section: Introductionmentioning
confidence: 99%
“…( 16 ) We selected this framework to guide intervention adaptation and implementation planning based on the explicit emphasis on discussing values and creating a participatory and equity-based space for leading the project, as well as an emphasis on praxis – using an intersectional lens to change systems. ( 20 22 ) Recent studies have demonstrated the value of the IBPA framework,( 22 24 ) exemplified by its application to the U.S. COVID-19 policy response;( 20 ) which underscores the growing significance of considerations of intersectionality in public health and highlights the transformative shift from analysis to actionable strategies.…”
Section: Introductionmentioning
confidence: 99%